2019
DOI: 10.1108/dlo-03-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Learning organization and work performance in Bandung city government in Indonesia: a path modeling statistical approach

Abstract: Purpose This study aims to explore the applicability of the learning organization (LO) concept as a predictor of work performance (WP) using partial least square (PLS) as a statistical method to explain the presence or absence of relationships between those latent variables. Design/methodology/approach An empirical approach was conducted on a research sample of a local government in Indonesia. The design of this study is a cross-sectional study using a closed-ended questionnaire, and PLS is used as a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The lifelong learning skills of employees are also associated with work performance [53,54]. The study by [55] reported that the concept of learning organizations positively predicted work performance. This relationship merits further investigation as it needed to be strengthened with more evidence from the workplace.…”
Section: Lifelong Learning and Work Performancementioning
confidence: 99%
“…The lifelong learning skills of employees are also associated with work performance [53,54]. The study by [55] reported that the concept of learning organizations positively predicted work performance. This relationship merits further investigation as it needed to be strengthened with more evidence from the workplace.…”
Section: Lifelong Learning and Work Performancementioning
confidence: 99%
“…Organizations that promote continuous learning expect their employees to be ultimately responsible for recognizing their own contextual performance as the organization provides required resources and enabling environment (Budhiraja, 2021;Anggara et al, 2019). The most cited work of Borman and Motowildo (1997) has recommended that contextual performance includes interpersonal skills, motivation to maintain good working relationships and help others perform their tasks.…”
Section: Continuous Learning and Employees' Contextual Performancementioning
confidence: 99%
“…Beberapa penelitian menjelaskan bahwa organisasi pembelajaran atau learning organization terbukti mempunyai pengaruh yang positif dan signifikan terhadap tingkat kinerja karyawan, seperti pendapat (Putri, 2020;Anggriawan & Rusilawati, 2014). Organisasi pembelajaran menjelaskan proporsi yang cukup besar terhadap peningkatan kinerja karyawan (Anggara, et al, 2019).…”
Section: Pendahuluanunclassified